CcpA Affects Infectivity of Staphylococcus aureus in a Hyperglycemic Environment - Bischoff, Markus; Wonnenberg, Bodo; Nippe, Nadine; Nyffenegger-Jann, Naja J.; Voss, Meike; Beisswenger, Christoph; Sunderkötter, Cord; Molle, Virginie; Dinh, Quoc Thai; Lammert, Frank; Bals, Robert; Herrmann, Mathias; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Many bacteria regulate the expression of virulence factors via carbon catabolite responsive elements. In Gram-positive bacteria, the predominant mediator of carbon catabolite repression is the catabolite control protein A (CcpA). Hyperglycemia is a widespread disorder that predisposes individuals to an array of symptoms and an increased risk of infections. In hyperglycemic individuals, the bacterium Staphylococcus aureus causes serious, life-threatening infections. The importance of CcpA in regulating carbon catabolite repression in S. aureus suggests it may be important for infections in hyperglycemic individuals. To test this suggestion, hyperglycemic non-obese diabetic (NOD; blood glucose level ≥20 mM) mice were challenged with the mouse pathogenic S. aureus strain Newman and the isogenic ccpA deletion mutant (MST14), and the effects on infectivity were determined. Diabetic NOD mice challenged with the ccpA deletion mutant enhanced the symptoms of infection in an acute murine pneumonia model relative to the parental strain. Interestingly, when diabetic NOD mice were used in footpad or catheter infection models, infectivity of the ccpA mutant decreased relative to the parental strain. These differences greatly diminished when normoglycemic NOD mice (blood glucose level ≤ 10 mM) were used. These data suggest that CcpA is important for infectivity of S. aureus in hyperglycemic individuals.